2015
DOI: 10.4103/2347-5625.152402
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of life of cancer patients undergoing chemotherapy: A questionnaire study

Abstract: Objective:This descriptive and cross-sectional study was undertaken to determine the factors affecting cancer patients’ quality of life.Methods:We collected data from 352 chemotherapy patients of an Outpatient Chemotherapy Unit in a state hospital. We included volunteered chemotherapy patients with a signed informed consent and at least 50 Karnofsky Performance Scale points. We gathered data by Personal Information Form and Nightingale Symptom Assessment Scale (N-SAS) and analyzed via basic descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
7
43
1
3
Order By: Relevance
“…Fatigue can influence the patients' treatment decisions and limit their self-care activities (Wright et al, 2015). Many personal and treatment-related factors influence fatigue and QoL in patients with cancer (Beijer, Kempen, Pijls-Johannesma, de Graeff, & Dagnelie, 2008;Dapueto, Servente, Francolino, & Hahn, 2005;McCabe, Grutsch, Braun, & Nutakki, 2015;Üstündağ & Zencirci, 2015). Psychological factors were found to influence patients' perceptions of fatigue symptoms (Kim et al, 2006;McCabe et al, 2015).…”
mentioning
confidence: 99%
“…Fatigue can influence the patients' treatment decisions and limit their self-care activities (Wright et al, 2015). Many personal and treatment-related factors influence fatigue and QoL in patients with cancer (Beijer, Kempen, Pijls-Johannesma, de Graeff, & Dagnelie, 2008;Dapueto, Servente, Francolino, & Hahn, 2005;McCabe, Grutsch, Braun, & Nutakki, 2015;Üstündağ & Zencirci, 2015). Psychological factors were found to influence patients' perceptions of fatigue symptoms (Kim et al, 2006;McCabe et al, 2015).…”
mentioning
confidence: 99%
“…The latter are associated with a higher risk of recurrence and poorer survival rates. Therefore, a correct pathological diagnosis is important for clinical treatment and prognosis (18)(19)(20). The present study identified a statistically significant and progressive increase in the expression of MCM7 with increasing grade and stage of papillary urothelial neoplasms.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, studies have indicated that patients with breast cancer had a worse social well-being than patients with other cancers [21]; therefore, considering the psychological factors in patients suffering from breast cancer is of great importance. The results of the present study indicated a significant negative association between type D personality and happiness and a positive association between type D personality and QOL (P<0.001), between positive cognitive strategies of emotion regulation and QOL and happiness (both P<0.001), and no significant relationship between negative cognitive strategies of emotion regulation and happiness and QOL (P=0.08).…”
Section: Discussionmentioning
confidence: 99%